We have u = < -3, 4> and v = < 4, 5>

=> u = -3i + 4j and v = 4i + 5j

3u + 2v

=> 3*(-3i + 4j) + 2*(4i + 5j)

=> -9i + 12j + 8i +10j

=> -i + 22j

u - v

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have u = < -3, 4> and v = < 4, 5>

=> u = -3i + 4j and v = 4i + 5j

3u + 2v

=> 3*(-3i + 4j) + 2*(4i + 5j)

=> -9i + 12j + 8i +10j

=> -i + 22j

u - v

=> -3i + 4j - 4i - 5j

=> -7i - j

**The required values are : 3u + 2v = -i + 22j and u - v = -7i - j**